Compact CPW fed electrically small antenna for WLAN application. Issue 2 (1st January 2014) - Deepak, U.; Roshna, T.K.; Nijas, C.M.; Mohanan, P.
Abstract : A compact coplanar waveguide (CPW) fed electrically small antenna suitable for 2.4 GHz WLAN applications is presented. The resonance of the structure is achieved by implanting a chip inductor in between the centre conductor of an open‐ended CPW transmission line and a short metal strip. The total electrical size of the fabricated antenna is 0.08 λ 0 × 0.0479 λ 0 . The reflection and radiation characteristics of the antenna and a method to enhance the gain are discussed.